High Resolution Melting (HRM) Analysis for Genetic Changes in BRCA1/2 gene - Samuel J Haryono; I Gusti Bagus Datasena; Ariananda Hariadi; Raymond Mulyarahardj (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
Conventional mutation analysis requires a separation step and include single-strand conformational polymorphism (SSCP) analysis, denaturing gradient gel electrophoresis, heteroduplex analysis, denaturing HPLC, and temperature gradient capillary electrophoresis These methods require separation of PCR products on a gel or other matrix, often take hours to perform, and increase the risk of contamination in future reactions because PCR products are exposed to the environment. High Resolution Melting (HRM) can simplify the mutation scanning analysis in BRCA 1/2 gene. DNA from affected patients and family members were amplified with Real-Time PCR reaction and followed by Sanger Sequencing to reconfirm the mutation status if mutation obtained by HRM Method. HRM Method was able to show distinction in differential curves of mutated BRCA 2 gene c.4600T>C, with codon modification of CAT>TAT, when compared to wildtype. To determine point mutation in a sample, this method requires two groups of experimental standards and standard curves. The first standard produced by using samples without mutation (wildtype/negative control) and the second standard produced by using samples with mutation (positive control), that have been confirmed with Sanger Sequencing. The sequencing analysis of the affected patient and the family members showed that a mutation occurred (BRCA2 c.4600T>C) and was segregated in the family history. This mutation caused amino acid alteration in BRCA2 protein (p.H1458Y). HRM Method is an excellent tool to analyze genetic modification of BRCA1/2 genes, especially to investigate co-segregation of mutated genes among family members of affected patient. This method can provide more sensitive results to determine mutation in patient, before using Sanger Sequencing analysis.Keyword: BRCA, HRM, Gene Mutation